2017
DOI: 10.1093/icesjms/fsw246
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ocean acidification and warming on the growth, calcification, and biophotonics of a California grass shrimp

Abstract: Cryptic colouration in crustaceans, important for both camouflage and visual communication, is achieved through physiological and morphological mechanisms that are sensitive to changes in environmental conditions. Consequently, ocean warming and ocean acidification can affect crustaceans’ biophotonic appearance and exoskeleton composition in ways that might disrupt colouration and transparency. In the present study, we measured growth, mineralization, transparency, and spectral reflectance (colouration) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…other species may have their exoskeletal mineral composition unaffected (Lowder et al, 2017), as observed for P. criniticornis in the current study, even under the combined stressors treatment. The ability to maintain, or even increase calcification rates and/or compensate dissolution rates when exposed to seawater acidification is well known amongst crustaceans (McDonald et al, 2009;Ries et al, 2009;Wickins, 1984), mollusks and echinoderms (Findlay et al 2011;Wood et al, 2008).…”
Section: Discussionsupporting
confidence: 50%
“…other species may have their exoskeletal mineral composition unaffected (Lowder et al, 2017), as observed for P. criniticornis in the current study, even under the combined stressors treatment. The ability to maintain, or even increase calcification rates and/or compensate dissolution rates when exposed to seawater acidification is well known amongst crustaceans (McDonald et al, 2009;Ries et al, 2009;Wickins, 1984), mollusks and echinoderms (Findlay et al 2011;Wood et al, 2008).…”
Section: Discussionsupporting
confidence: 50%
“…Among marine invertebrates, crustaceans, and especially decapods, are considered to be among the least affected calcifying species by the exposure to low pH/high p CO 2 conditions [ 8 , 12 ] in terms of survival, growth, metabolism, acid-base balance, carapace mineralisation, and behaviour [ 21 , 22 , 23 , 24 , 25 , 26 ]. While different species can show opposite responses [ 27 , 28 ], this overall low sensitivity to OA may be linked to crustaceans homeostatic and regulatory abilities, their capacity to relocate exoskeletal calcium (Ca 2+ ) and carbonate (CO 3 2− ) ions during moulting, and their impermeable cuticle protecting the carapace from dissolution and limiting exchanges with the surrounding environment [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mantis shrimps did not show any changes in their survival or growth following exposure to reduced pH of 7.57 for 6 months (DeVries et al, 2016). Lowder et al (2017) reported that California grass shrimps exposed to a pH of 7.48 survived 7 weeks without any significant difference in carapace length compared to the controller group (pH of 7.98). Other studies documented negative impacts at similar low pH levels.…”
Section: Discussionmentioning
confidence: 93%